2002
DOI: 10.1074/jbc.m200058200
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin-Radixin-Moesin-binding Phosphoprotein-50/Na+/H+ Exchanger Regulatory Factor (EBP50/NHERF) Blocks U50,488H-induced Down-regulation of the Human κ Opioid Receptor by Enhancing Its Recycling Rate

Abstract: We have investigated whether Ezrin-radixin-moesin (ERM)-binding phosphoprotein-50/Na؉ /H ؉ exchanger regulatory factor (EBP50/NHERF), a PDZ domain-containing phosphoprotein, is associated with the human opioid receptor (hkor) and whether it regulates the trafficking and signaling of the hkor. To determine the motif of FLAG-hkor involved in EBP50/NHERF binding, we generated two mutants, FLAG-hkor-A and FLAG-hkor-EE, in which one Ala or two Glu residues were added to the C terminus, respectively. Neither FLAG-hk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 44 publications
4
116
3
Order By: Relevance
“…EBP50 has been shown to stabilize GPCRs, including b2-adrenergic, PTH and k-opioid receptors, at the membrane by tethering these proteins to membrane cytoskeleton via ezrin, and therefore reducing receptor internalization. 8,9,39 This conclusion was based on an EBP50 mutant deleted of its ezrinbinding region, which had also lost membrane-tethering capacity. However, we were unable to identify an EBP50-deletion mutant that had this type of regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBP50 has been shown to stabilize GPCRs, including b2-adrenergic, PTH and k-opioid receptors, at the membrane by tethering these proteins to membrane cytoskeleton via ezrin, and therefore reducing receptor internalization. 8,9,39 This conclusion was based on an EBP50 mutant deleted of its ezrinbinding region, which had also lost membrane-tethering capacity. However, we were unable to identify an EBP50-deletion mutant that had this type of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 EBP50 binds proteins that contain a PDZ-binding motif including ion exchangers, 4,5 ion channels, 6 G protein-coupled receptors, [7][8][9] growth factor tyrosine kinase receptors 10,11 and PTEN. 10 EBP50 participates in the modulation of ion transport, organization of apical microvilli, cancer development, and the trafficking and stabilization of membrane proteins.…”
mentioning
confidence: 99%
“…Although 13 of the tails in the library end in a type 1 PDZ recognition sequence (Table II), none of these tails bound EBP50. It has been suggested that EBP50 could be involved in the recycling of the KOP receptor, which does not contain a PDZ recognition sequence, as demonstrated by co-immunoprecipitation experiments (47). However, neither the KOP receptor tail nor any of the other tails in the library bound EBP50 (Fig.…”
Section: Tm Receptor Tails and Post-endocytic Adaptor Proteinsmentioning
confidence: 99%
“…4B). Considering that the complex-glycosylated form stability reflects the overall characteristic of post-Golgi, cell surface, and endosomal CFTR pools, and NHERF may facilitate recycling of CFTR as observed for G-protein-coupled receptors (24,26,35,50), next we evaluated the effect of C-terminal truncation on the apical localization and channel function of CFTR.…”
Section: Cftr-nherf Interaction Is Dispensable For the Stability Of Tmentioning
confidence: 99%
“…The D1 and D2 domains bind with nanomolar affinity to the PDZbinding motifs of CFTR ( 1477 DTRL) and to the C terminus of other transport proteins, signaling molecules, and receptors (18,(22)(23)(24)(25)(26). The ERM-binding domain tethers the complex via ezrin to cytoskeletal elements in a phosphorylation-dependent manner and to the catalytic and regulatory subunit of PKA (19,(27)(28)(29).…”
mentioning
confidence: 99%